Recombinant Nematode Anticoagulant Protein c2, a Novel Inhibitor of Tissue Factor-Factor VIIa Activity, Abrogates Endotoxin-Induced Coagulation in Chimpanzees - Moons, Arno H. M.; Peters, Ron J. G.; Cate, Hugoten; Bauer, Kenneth A.; Vlasuk, George P.; Büller, Harry R.; Levi, Marcel (Thrombosis and Haemostasis, 2002)
Systemic activation of coagulation leading to disseminated intravascular coagulation (DIC) is an important feature in patients with severe sepsis. Tissue factor has been shown to play a primary role in this pathological response, as revealed by the use of specific inhibitors and antagonists of the tissue factor/factor VIIa pathway. This class of agents has been demonstrated to attenuate the coagulation response in human volunteers with induced low-grade endotoxemia and to reduce mortality in primate models of Gram-negative sepsis. The efficacy of these agents in attenuating the activation of coagulation and formation of microvascular thrombosis in sepsis may depend on the mechanism of inhibition. Here we demonstrate the efficacy of recombinant nematode anticoagulant protein c2 (rNAPc2) that specifically inhibits the tissue factor/factor VIIa complex by a novel mechanism, in a model of endotoxin-induced coagulation activation in chimpanzees.Administration of a low dose of Gram-negative endotoxin induced marked increases of thrombin generation as measured by plasma levels of prothrombin activation fragment F1+2 and thrombin-antithrombin complexes, which were completely blocked by rNAPc2. In chimpanzees receiving rNAPc2 alone, there was a significant reduction in the activation of factor X but not factor IX, compared to animals receiving placebo. In contrast to the effect of rNAPc2 on thrombin generation, there was no effect of this inhibitor on the well known enhanced systemic fibrinolytic response induced by endotoxin.In conclusion, the recombinant peptide rNAPc2 is an effective inhibitor of tissue factor-driven thrombin generation during low grade endotoxemia. These results suggest that rNAPc2 may be a promising therapeutic option to inhibit coagulation activation in patients with sepsis.
Keywords: rNAPc2; endotoxin; tissue factor/factor VIIa; thrombin generation; chimpanzees